Cardiopulmonary resuscitation. Paper 1: A survey of undergraduate training in UK medical schools. Issue 3 (September 1994) - Graham, C A; Guest, K A; Scollon, D
Abstract : This paper presents the results of a UK national survey of Basic Life Support (BLS) and Advanced Cardiac Life Support (ACLS) training for undergraduate medical students. In all responding medical schools, undergraduates are taught BLS at least once during their course but the assessment and refresher aspects of BLS training are not uniformly covered. There are inconsistencies in ACLS teaching, with some schools providing formal courses, some teaching specific techniques and others providing no ACLS teaching. Most interestingly, of those completing the questionnaire, only 52% considered present undergraduate training adequate to enable junior house officers to provide an effective resuscitation service. We recommend that all aspects of BLS and ACLS training for medical undergraduates be improved and standardized throughout the UK.